Disentangling above- and below-ground facilitation drivers in arid environments the role of soil microorganisms, soil properties and microhabitat - Lozano, Yudi M (The New phytologist, 2017)
© 2017 The Authors. New Phytologist © 2017 New Phytologist Trust.